Swimming performance of Arctic grayling (Thymallus arcticus Pallas) in an open-channel flume. Issue 1 (2nd January 2020) - Dockery, David R.; Ryan, Erin; Kappenman, Kevin M.; Blank, Matt
Abstract: Installing effective fish passage structures that provide connectivity for Arctic grayling is a promising conservation strategy for imperiled populations. The swimming abilities and behaviour of age 1+ adfluvial grayling from Montana were examined in an open-channel flume to provide design information for passage structures. Swimming behaviours and distance of ascent (Dmax) in a 12.25 m section was measured at four velocities (0.49, 1.04, 1.43, 2.26 m/s) at an average temperature of 11.3 °C (SD = 0.7); effects of fish length and time of day were also examined. Median Dmax was equal to 12.25 m for all treatments except the 2.26 m/s treatment, where it dropped to 4.5 m. Average fish swimming velocities increased from 0.85 to 2.97 m/s from the lowest to the highest velocity treatments and the maximum velocity observed was 4.03 m/s. Survival model parameterization allowed prediction of the proportion passing relative to distance for covariate values within the range tested. There was strong evidence Dmax was related to water velocity (p < 0.001) and an 82% decrease in Dmax is estimated for every 1 m/s increase in water velocity. There was no evidence for relationships among distance of ascent and fish length (p = 0.91) or time of day (p = 0.81).